Incidencia de la carga fiscal en la desigualdad en los países de América Latina y el Caribe: un estudio con datos panel y cointegración - Mora Ordoñez, Karen Guissella (2022)
Inequality is a latent problem worldwide, encompassing a number of difficulties that arise from the development of economies. For Piketty (2014), one way to counteract inequality is through taxes, which is why the objective of this research is to evaluate the existence of a long-term equilibrium relationship and causality between income inequality and the fiscal burden in the countries of Latin America and the Caribbean in the period 1995-2016, using the panel data econometric technique. The data was obtained from the World Bank (2018) and the Economic Freedom database (2020). It was obtained as results that there is a long-term equilibrium relationship between the study variables. In addition, there is no bidirectional causality, that is, it goes from inequality to the tax burden and vice versa. Based on these results, public policies can be applied aimed at reducing income inequality, first public investment policies; second, policies that control the informality of the economies; third, investment in social protection programs; fourth, creation of an equitable and inclusive State.